2013
DOI: 10.3390/jlpea3020054
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Sub-VT and Near-VT 2T Gain-Cell Memories for Ultra-Low Power Applications under Technology Scaling

Abstract: Ultra-low power applications often require several kb of embedded memory and are typically operated at the lowest possible operating voltage (VDD) to minimize both dynamic and static power consumption. Embedded memories can easily dominate the overall silicon area of these systems, and their leakage currents often dominate the total power consumption. Gain-cell based embedded DRAM arrays provide a high-density, low-leakage alternative to SRAM for such systems; however, they are typically designed for operation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 21 publications
2
28
0
Order By: Relevance
“…The spice net-lists of the 2T and 3T1D gain-cells are simulated in HSPICE [18] circuit simulator. The e-DRAMs were shown to perform reliably in nearthreshold region at 40nm node in [16]. So in this paper, e-DRAM gain-cells are studied at the next scaled technology node 32nm (using HP PTM models [19]) which is going to be the technology node for the future sub-threshold circuit implementations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The spice net-lists of the 2T and 3T1D gain-cells are simulated in HSPICE [18] circuit simulator. The e-DRAMs were shown to perform reliably in nearthreshold region at 40nm node in [16]. So in this paper, e-DRAM gain-cells are studied at the next scaled technology node 32nm (using HP PTM models [19]) which is going to be the technology node for the future sub-threshold circuit implementations.…”
Section: Methodsmentioning
confidence: 99%
“…As an alternative to SRAM bit-cells, Meinerzhagen et.al. [16] investigated sub-threshold 2T e-DRAM gain-cells for ultra-low power medical applications. Their study showed reliable operation for 2kb e-DRAM array up to sub-threshold voltage of 0.4V at mature 0.18µm node and up to near-threshold voltage of 0.6V at scaled 40nm node.…”
Section: Introductionmentioning
confidence: 99%
“…This level can be read out by predischarging the read bitline (RBL) and subsequently raising the read wordline (RWL), conditionally charging RBL if the voltage level stored on SN is low. The circuit's leakage power, shown to be dominated by subthreshold conduction at submicron process technologies [4], is extremely low, since during standby and write, the drain-to-source voltage (V DS ) of MR is zero, and the subthreshold leakage through MW is limited to (dis)charging the storage capacity of SN. The obvious issue is that any leakage to or from SN results in a degradation of the stored data level, requiring periodic refresh cycles.…”
Section: Replica Technique For Auto-refresh Timing a Retention Tmentioning
confidence: 99%
“…Furthermore, the subthreshold leakage to/from C SN is exponentially dependent on the overdrive of MW, which is constant for the worst-case of '0' storage (WBL=V DD ) but self limiting in the case of '1' degradation (WBL=0, V SG = V SN − V DD ). A full description of these processes is presented in [4].…”
Section: B Replica Technique Conceptmentioning
confidence: 99%
See 1 more Smart Citation